150 years of boom and bust: what drives mineral commodity prices? - Martin Stürmer (Deutsches Institut für Entwicklungspolitik (DIE), 2013)
This paper examines the dynamic effects of demand and supply shocks on mineral commodity prices. It provides empirical insights by using annual data for the copper, lead, tin, and zinc markets from 1840 to 2010. I identify structural shocks by using long-run restrictions and compare these shocks to narrative historical evidence about the respective markets. Long-term price fluctuations are mainly driven by persistent demand shocks. Supply shocks exhibit some importance in the tin and copper markets due to oligopolistic market structures. World output-driven demand shocks have persistent, positive effects on mineral production. Long-term linear trends are statistically insignificant or significantly negative for the examined commodity prices. My results suggest that the current price boom is temporary but not permanent. Commodity exporting countries should prepare for a downswing of prices, while commodity importing countries should not fear for the security of supply of these widely used mineral commodities.
Keywords: 330; Deutsche + Europäische + multilaterale Entwicklungspolitik; Energie; Umwelt; Ökosysteme und Ressourcen